(untitled) (Malaysian Journal of Civil Engineering, 2018)
This paper presents the seismic hazard assessment which involved spectral hazard for 10 % probability of exceedance in 50 years or correspond to return period of approximately 475 years for bedrock of Kuala Lumpur city. The analysis was performed using the total probability theorm with 2D seismic source model. Time history data for this site was generated synthetically by modifying the existing time history data using spectral matching analysis. In this study, design response spectra were developed by applying the methods proposed by 1997 NEHRP. The final result are the spectral accelaration and the synthetic time histories on the bedrock, and the design response spectra on Kuala Lumpur ground surface for 475 years return periods.